Representation of Single Father Image in McDonald's: Still My Little Girl Advertisement - Cindy Fransisca Santoso (Institute of Research and Community Outreach - Petra Christian University, 2022)
Many advertisements employ gender stereotypes to attract people nowadays. If advertisers continue to employ and display a specific gender in their advertisements, it might lead to gender bias. Through verbal and visual expressions in McDonald's: Still My Little Girl advertisement, this study seeks to discover a depiction of a single father, and he can replace the mother's role in the family. The writer uses semiotic theory and a qualitative approach to analyze the data. The findings indicate that a father who is portrayed as the main character can replace the role of a mother in performing household tasks and dealing with his daughter's sensitive situations.